Immunolocalization of an amino-terminal fragment of apolipoprotein E in the Pick's disease brain. - Troy T Rohn; Ryan J Day; Lindsey W Catlin; Raquel J Brown; Alexander J Rajic; Wayne W Poon (PLoS ONE)
Although the risk factor for apolipoprotein E (apoE) polymorphism in Alzheimer's disease (AD) has been well described, the role that apoE plays in other neurodegenerative diseases, including Pick's disease, is not well established. To examine a possible role of apoE in Pick's disease, an immunohistochemical analysis was performed utilizing a novel site-directed antibody that is specific for an amino-terminal fragment of apoE. Application of this antibody, termed the amino-terminal apoE cleavage fragment (nApoECF) antibody, consistently labeled Pick bodies within area CA1 of the hippocampus in 4 of the 5 cases examined. Co-localization of the nApoECF antibody with PHF-1, a general marker for Pick bodies, as well as with an antibody to caspase-cleaved tau (TauC3) was evident within the hippocampus. While staining of the nApoECF antibody was robust in area CA1, little co-localization with PHF-1 in Pick bodies within the dentate gyrus was observed. A quantitative analysis indicated that approximately 86% of the Pick bodies identified in area CA1 labeled with the nApoECF antibody. The presence of truncated apoE within Pick bodies suggests a broader role of apoE beyond AD and raises the question as to whether this protein contributes to pathogenesis associated with Pick's disease.